Carcass and meat characteristics from farm-raised and wild fallow deer (Dama dama) and red deer (Cervus elaphus): A review - Kudrnáčová, Eva; Bartoň, Luděk; Bureš, Daniel; Hoffman, Louwrens C (Meat science, 2018)
Deer species are utilised for food, hunting and other products throughout the world. Consumers are typically exposed to venison derived predominantly from both farm-raised or wild fallow (Dama dama) and red deer (Cervus elaphus). The production of venison under farm conditions, compared to the meat of deer hunted in the wild, allows for a regular supply of a consistently good meat. It is lean, tasty, and rich in proteins and minerals, with a low content of fat and cholesterol. Overall, the worldwide demand for meat is still growing, and both the potential of farming deer species and their use as meat producers have led to an increased interest in venison. The current knowledge about various factors (e.g. nutrition, age, sex, condition, season) affecting venison and game meat has significantly increased during past decades but information regarding the interaction between production system or pre- and post-slaughter handling and ultimate deer meat quality are still very limited.
Keywords: farmy; Animals, Wild; Venison; Farms; Animal Husbandry; Nutrition; maso; mužské pohlaví; vysoká zvěř; Performance; složení těla; chov zvířat; divoká zvířata; ženské pohlaví; zvířata; Meat quality; Meat; Deer; Species Specificity; Cervidae; druhová specificita; Body Composition; Female; Male; Animals